Toward auto-netnography in consumer studies. (November 2020) - Coombes, Philip H; Jones, Scott
The purpose of this article is to offer an argument for a wider acceptance and adoption of online auto-ethnography—or auto-netnography as an alternative social media research method to online ethnography—or netnography—when undertaking consumer research. As an online research method, netnographies have attracted increasing attention from researchers in various inter-disciplinary studies during recent years, but the method is still not considered mainstream. While the proliferation of online communities using various social media platforms is increasingly supporting consumers when making product/service choices, the adoption of netnographies appears to leave room for an extension toward the consideration by consumer researchers of how auto-netnography could highlight these researchers' own personal experiences in online communities. Auto-netnography allows the researcher to capture their own online experiences as a consumer would through social observation, reflexive note-taking, and other forms of data. Contemporary technology can also provide a more innovative approach with artificial intelligence offering an alternative dimension. We contend there is a need for consumer researchers—both academic and practitioner—to further reflect on and discuss the deployment of auto-netnography to contribute to further exploration of online communities through the qualitative lens.